Asthma in elderly in Turkey: a multicenter study - Gemicioglu, B.; Mungan, D.; Ogus, C.; Erkekol, Oner F.; Dursun, B.; Saka, D.; Yildiz, F. (Wiley-Blackwell, 2012)
[Abstract Not Available]
31st Congress of the European-Academy-of-Allergy-and-Clinical-Immunology (EAACI) -- JUN 16-20, 2012 -- Geneva, SWITZERLAND